2013
DOI: 10.1254/jphs.12241fp
|View full text |Cite
|
Sign up to set email alerts
|

Rat Submandibular Gland Perfusion Method for Clarifying Inhibitory Regulation of GABAA Receptor

Abstract: Abstract. GABA is an inhibitory transmitter found in rat salivary gland. However, the inhibitory potential of GABA on salivary secretion is unclear. Using an in vivo cannulation method, intraperitoneal administration of GABA was ineffective in the absence of gabaculine, a GABA transaminase inhibitor, on pilocarpine-induced salivary secretion, suggesting that GABA was rendered metabolically inactive before reaching the salivary gland. We hypothesized that the action of a drug on the salivary glands could be mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…GABA A receptors can be both central and peripheral (located in the salivary glands) (Okubo and Kawaguchi, 2013 ). Kosuge et al ( 2009 ) demonstrated the presence of peripheral GABA A receptors in the acinar cells of parotid and submandibular glands of rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GABA A receptors can be both central and peripheral (located in the salivary glands) (Okubo and Kawaguchi, 2013 ). Kosuge et al ( 2009 ) demonstrated the presence of peripheral GABA A receptors in the acinar cells of parotid and submandibular glands of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, both on human and animals, have demonstrated that BZDs cause a reduction in salivary flow, with severe oral side effects (De Almeida Pdel et al, 2008 ; Femiano et al, 2008 ). BZDs act to induce reduction in salivary flow through GABA A receptors located in the salivary glands as well as through indirect actions of the CNS on the salivary glands mediating central GABA A receptors (Kujirai et al, 2002 ; Okubo and Kawaguchi, 2013 ). In addition to inhibiting the muscarinic receptors present in the salivary glands, which are responsible for the salivary flow, BZDs also can affect the transport of chloride and the calcium influx, which can lead to fluid secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in contrast to the fact that most physiological studies on the effect of GABA in the saliva secretion have been done in adult rodents (Okubo & Kawaguchi, 2013;Ouchi et al, 2011). From this chronological feature of the present immunoreactivity, it is more plausible to consider the regulatory role of GABA in the development of the glandular cells rather than the saliva…”
Section: Resultsmentioning
confidence: 57%
“…Our group has already reported on the mechanism underlying this side effect in a number of earlier studies. Central‐ and peripheral‐type BDZ receptors were involved in suppression of salivary secretion induced by cholinergic or adrenergic stimulation in rat salivary gland (Yamagishi and Kawaguchi, ; Okubo and Kawaguchi, , ). Another study demonstrated that DZP increased intracellular Cl − levels by preventing Ca 2+ release from intracellular calcium ([Ca 2+ ] i ) stores, and suppressed Cl − efflux through Ca 2+ ‐dependent Cl − channels in the apical membrane of acinar cells (Kawaguchi and Yamagishi, ; Kujirai et al , ).…”
Section: Introductionmentioning
confidence: 99%